The Effect Of The Psychological Work Environment On The Performance Of Employees With Work Stress As A Variable Intervening : Sales Division Employee At PT. Good Sale Tech - Moh Rozi Bapadal; Koen Irianto Uripan; Sutomo; Siti Nur Soleha; Ahmad Zainuddin (PT Maju Malaqbi Makkarana, 2026)
The work environment is an organizational element as a social system that has a strong influence on the formation of individual interests in the organization and affects organizational achievement. The work environment itself consists of a physical and non-physical work environment that is inherent in employees, so that it cannot be separated from efforts for employee performance and avoiding employee work stress. The purpose of the study was to determine the influence of the psychological work environment on employee performance, with work stress as an intervening variable, in Sales Division Employees at PT. Good Sale Tech. This study uses a quantitative approach with a survey method. The results of the study showed that the work environment had a positive and significant effect on employee performance, the work environment had a positive and significant effect on employee work stress, and the work environment had a significant positive effect on employee performance and work stress. Work stress can mediate the relationship between the psychological work environment and performance, where stress arises due to a high workload and affects employee performance in a decreasing manner.